Equity and Renewable Energy: An Analysis in Residential Users in the Department of Atlántico-Colombia - Grimaldo Guerrero, John William; Jimenez Rios, Carlos; Muñoz del Villar, Lony; Gomez Carreño, Elio; Bolaño Turyol, Jorge (International Journal of Energy Economics and Policy, 2021)
Sustainable development has its complexity in seeking a balance between the three dimensions, renewable energies require an economic investment and are friendly to the environment; but due to socioeconomic differences, access and widespread use may be limited. Colombia has a subsidy mechanism according to socioeconomic strata, where the lower strata receive a reduction in the price of energy by a set amount of kWh, while the upper strata contribute a 20% of the final price. This research performs an economic evaluation due to the investment made in a photovoltaic system, considering socioeconomic factors; The results will make it possible to identify factors that affect equity and access to these technologies. Keywords: Energy policy, Barriers, Equity, Renewable energy. JEL Classifications: K29, Q48 DOI: https://doi.org/10.32479/ijeep.11092